Impact of intended and relative dose intensity of R‐CHOP in a large, consecutive cohort of elderly diffuse large B‐cell lymphoma patients treated with curative intent: no difference in cumulative incidence of relapse comparing patients by age. (11th April 2019) - Eyre, T. A.; Martinez‐Calle, N.; Hildyard, C.; Eyre, D. W.; Plaschkes, H.; Griffith, J.; Wolf, J.; Fields, P.; Gunawan, A.; Oliver, R.; Djebbari, F.; Booth, S.; et al.
Abstract: Background: The increasing incidence of diffuse large B‐cell lymphoma (DLBCL) in ageing populations places a significant burden on healthcare systems. Co‐morbidity, frailty, and reduced organ and physiological reserve contribute to treatment‐related complications. The optimal dose intensity of R‐CHOP to optimize outcome across different ages with variable frailty and comorbidity burden is unclear. Objectives and Methods: We examined the influence of intended (IDI) and relative (RDI) dose intensity of the combination of cyclophosphamide and doxorubicin, age and comorbidity on outcomes for DLBCL patients ≥70 years in a representative, consecutive cohort across eight UK centres (2009–2018). We determined predictors of survival using multivariable Cox regression, and predictors of recurrence before death using competing risks regression. Results: Porgression‐free survival (PFS) and overall survival (OS) were significantly inferior in patients ≥80 vs. 70–79 years ( P  < 0.001). In contrast, 2‐year cumulative relapse incidence, when accounting for non‐relapse mortality as a competing risk, was no different between 70–79 vs. ≥80 years ( P  = 0.27) or comorbidity status (CIRS‐G: 0–6 vs. >6) ( P  = 0.27). In 70–79 years, patients with an IDI ≥80% had a significantly improved PFS and OS ( P  < 0.001) compared to IDI < 80%. Conversely, in patients ≥80 years, there was no difference in PFS ( P  = 0.88) or OS ( P  = 0.75) according to IDI <80% vs. ≥80%. On multivariable analysis, when comparing by age, there was a significantly higher cumulative relapse rate for patients aged 70–79 years with an IDI <80% (vs. >80%) ( P  = 0.04) but not for patients ≥80 years comparing IDI ( P  = 0.32). Conclusion: 'R‐mini‐CHOP' provides adequate lymphoma‐specific disease control and represents a reasonable treatment option in elderly patients ≥80 years aiming for cure. Abstract :